Assessing symptom burden using the M. D. Anderson symptom inventory in patients with chemotherapy-induced anemia: results of a multicenter, open-label study (SURPASS) of patients treated with darbepoetin-alpha at a dose of 200 microg every 2 weeks - Gabrilove, Janice L; Perez, Edith A; Tomita, Dianne K; Rossi, Greg; Cleeland, Charles S (Cancer, 2007)
Patients with cancer who are receiving chemotherapy often experience chemotherapy-induced anemia (CIA), which is associated with symptoms that reduce quality of life. The M. D. Anderson Symptom Inventory (MDASI) is a brief, self-rating assessment scale that measures the severity of core symptoms and symptom interference with function. The current study used the MDASI to prospectively assess the correlation between hemoglobin and self-perceived cancer-related symptoms in a large patient population with CIA who were receiving darbepoetin-alpha at a dose of 200 mug every 2 weeks. Eligible patients enrolled in this multicenter, open-label study were age > or =18 years, had a nonmyeloid malignancy, were receiving multicycle chemotherapy, and were anemic (hemoglobin < or = 11 g/dL). Hemoglobin was measured every 2 weeks; the MDASI was administered weekly. For hemoglobin-based endpoints, patients were stratified by baseline hemoglobin (< 10 g/dL or > or =10 g/dL). Of 2422 enrolled patients, 2401 received > or =1 dose of darbepoetin-alpha. Eighty percent of patients (95% confidence limit, 78-82 patients) achieved target hemoglobin levels (> or =11 g/dL) during the study. Patients with a baseline hemoglobin < 10 g/dL had a greater increase in hemoglobin, took longer to achieve the target hemoglobin, and received more red blood cell transfusions than patients with a baseline hemoglobin > or =10 g/dL. The percentage of patients with moderate to severe MDASI scores (> or =5 points) for fatigue, distress, loss of appetite, disturbed sleep, and interference with function was reduced during the study. Improvement in symptom burden was associated with an increase in hemoglobin concentration. Treatment with darbepoetin-alpha at a dose of 200 mug every 2 weeks is associated with improvement in symptom burden as measured by the MDASI, a simple tool that may improve symptom management for cancer patients with CIA.